Potential Packaging and Distribution Channel Model for Rural Tourism Packages in Timpag Village, Kerambitan District, Tabanan Regency, Bali - Suryawati, Dewa Ayu; Flaviana Osin, Rosvita (Akademi Komunitas MAPINDO, 2023)
In terms of natural potential, cultural potential, and man-made potential, the Timpag resort region of TabananRegency has respectable potential to be developed as a tourist resort. The aim of this research is to find possiblerural tour package models, packaging options, and distribution channels in Timpag Village, Tabanan Regency.This research is a type of qualitative research that collects data through techniques such as in-depth interviewsand conducting literature studies in addition to direct observation at the research site (observation). Bypresenting the findings of the in-depth interviews to the informants, especially the Perbekel, Pokdarwis, andTimpag Village residents, the data is presented in the form of a description. From the results of in-depthinterviews, observations and studies of secondary data that the main drivers of tourism sustainability inTimpag Village are natural potential, cultural potential and man-made potential. The development of naturaltourism involves organizing numerous agricultural pursuits into a singular appeal (USP) that can be promoted.This cultural potential offers a religious destination in the form of a shower with seven springs and shows thelife of farmers to tourists. Tourists are invited to get to know the local culture by being welcomed by thePanyembrama dance. The artificial potential in Timpag village through unique and unique crafts can become atourist destination for village souvenirs. The direct marketing distribution channel model is used to marketrural tour packages in Timpag Village. This involves the use of digital media as well as intermediaries whichinclude marketing agencies such as tour drivers, tour guides, travel agents and local marketers.Keywords: Identify the Potential, Packaging, Tourism Village